Self‐management of first trimester medical termination of pregnancy: a qualitative study of women's experiences. (14th June 2017) - Purcell, C; Cameron, S; Lawton, J; Glasier, A; Harden, J
Abstract : Objective: To explore the experiences of women in Scotland who return home to complete medical termination of pregnancy (TOP) ≤63 days of gestation, after being administered with mifepristone and misoprostol at an NHS TOP clinic. Design: Qualitative interview study. Setting: One National Health Service health board (administrative) area in Scotland. Population or Sample: Women in Scotland who had undergone medical TOP ≤63 days, and self‐managed passing the pregnancy at home; recruited from three clinics in one NHS health board area between January and July 2014. Methods: In‐depth, semi‐structured interviews with 44 women in Scotland who had recently undergone TOP ≤63 days of gestation, and who returned home to pass the pregnancy. Data were analysed thematically using an approach informed by the Framework method. Main outcome measures: Women's experiences of self‐management of TOP ≤63 days of gestation. Results: Key themes emerging from the analysis related to self‐administration of misoprostol in clinic; reasons for choosing home self‐management; facilitation of self‐management and expectation‐setting; experiences of getting home; self‐managing and monitoring treatment progress; support for self‐management (in person and remotely); and pregnancy self‐testing to confirm completion. Conclusions: Participants primarily found self‐administration of misoprostol and home self‐management to be acceptable and/or preferable, particularly where this was experienced as a decision made jointly with health professionals. The way in which home self‐management is presented to women at clinic requires ongoing attention. Women could benefit from the option of home administration of misoprostol. Tweetable abstract: Women undergoing medical TOP 63 days found home self‐management to be acceptable and/or preferable. Tweetable abstract: Women undergoing medical TOP 63 days found home self‐management to be acceptable and/or preferable.